Reservoir quality and facies modeling of the early Eocene carbonate stratigraphic unit of the Middle Indus Basin, Pakistan - Khalid, Perveiz; Ehsan, Muhammd Irfan; Khurram, Shahzada; Ullah, Irfan; Ahmad, Qazi Adnan (Frontiers in Earth Science, 2022)
The Early Eocene carbonate reservoir, Sui Main Limestone (SML), is the largest gas reservoir of Pakistan. In Qadirpur area, more than 30 wells drilled, some of these were declared dry or abundant due to poor reservoir character or facies variation. The aim of this work is to re-evaluate the reservoir character and facies identification of SML by using petrophysical analysis and rock physics modeling in the Qadirpur field, Middle Indus Basin of Pakistan. The reservoir characterization of carbonate rocks is difficult task because of their complex pore networking. The well data of five exploratory wells drilled in this gas field is used. The log derived porosity varies in a very large range 2% – 36% with an average porosity 14 % – 34 %. The average porosity of the clean carbonate intervals is about 10 – 14%, thus it has the ability to accumulate hydrocarbon. The high porosity value indicates the presence of micro-fractures in the SML. These micro-fractures and secondary pores are well interconnected and allow the pore fluids to communicate. The secondary porosity is mainly due to the presence of vuggs and fractures in the SML. The volume of shale varies 11% – 38 % in the wells. The net pay zones have hydrocarbon saturation in the range of 40 – 70% which is mainly gas. On the basis of wireline log response, the formation is divided into three facies: limestone, shale and shaly limestone. This comprehensive work may help to improve the prediction of the reservoir quality in heterogeneous carbonate reservoirs and optimum field development.